Prognosis of Epizootic Activity of Natural Plague Foci in the Russian Federation for the Year of 2010 - N. V. Popov; V. E. Bezsmertny; V. P. Toporkov; S. M. Ivanova; A. I. Udovikov; A. A. Kuznetsov; T. V. Knyazeva; L. D. Shilova; V. V. Kutyrev (Проблемы особо опасных инфекций, 2010)
Short-term prognosis of epizootic activity of 11 natural plague foci in Russia for 2010 is substantiated. The analysis of the main plague carries and vectors abundance in natural foci of different types was carried out. Determined were the modern tendencies of the dynamics of epizootic activity of natural plague foci with different biocenotic structure.